Comprehensive analysis of tobacco pollen transcriptome unveils common pathways in polar cell expansion and underlying heterochronic shift during spermatogenesis - Hafidh, Said; Breznenová, Katarína; Růžička, Petr; Feciková, Jana; Capková, Věra; Honys, David (Bmc plant biology, 2012)
BACKGROUND: Many flowering plants produce bicellular pollen. The two cells of the pollen grain are destined for separate fates in the male gametophyte, which provides a unique opportunity to study genetic interactions that govern guided single-cell polar expansion of the growing pollen tube and the coordinated control of germ cell division and sperm cell fate specification. We applied the Agilent 44 K tobacco gene chip to conduct the first transcriptomic analysis of the tobacco male gametophyte. In addition, we performed a comparative study of the Arabidopsis root-hair trichoblast transcriptome to evaluate genetic factors and common pathways involved in polarized cell-tip expansion. RESULTS: Progression of pollen grains from freshly dehisced anthers to pollen tubes 4 h after germination is accompanied with > 5,161 (14.9%) gametophyte-specific expressed probes active in at least one of the developmental stages. In contrast, > 18,821 (54.4%) probes were preferentially expressed in the sporophyte. Our comparative approach identified a subset of 104 pollen tube-expressed genes that overlap with root-hair trichoblasts. Reverse genetic analysis of selected candidates demonstrated that Cu/Zn superoxide dismutase 1 (CSD1), a WD-40 containing protein (BP130384), and Replication factor C1 (NtRFC1) are among the central regulators of pollen-tube tip growth. Extension of our analysis beyond the second haploid mitosis enabled identification of an opposing-dynamic accumulation of core regulators of cell proliferation and cell fate determinants in accordance with the progression of the germ cell cycle. CONCLUSIONS: The current study provides a foundation to isolate conserved regulators of cell tip expansion and those that are unique for pollen tube growth to the female gametophyte. A transcriptomic data set is presented as a benchmark for future functional studies using developing pollen as a model. Our results demonstrated previously unknown functions of certain genes in pollen-tube tip growth. In addition, we highlighted the molecular dynamics of core cell-cycle regulators in the male gametophyte and postulated the first genetic model to account for the differential timing of spermatogenesis among angiosperms and its coordination with female gametogenesis.
Keywords: Gene Knockdown Techniques; kořeny rostlin; Plant Roots; Pollen Tube; Arabidopsis; gametogeneze rostlin; buněčný cyklus; Cell Cycle; Transcriptome; Nicotiana; klíčení; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; pylová láčka; RNA, Plant; Oligonucleotide Array Sequence Analysis; regulace genové exprese u rostlin; vývojová regulace genové exprese; Pollen; Gene Expression Regulation, Plant; pyl; RNA rostlin; genový knockdown; Gametogenesis, Plant; transkriptom; Germination; Gene Expression Regulation, Developmental; tabák